Rural Finance and Developments in Philippine Rural Financial Markets: Issues and Policy Research Challenges - Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2004)
The shift to a market-oriented credit and financial policy was expected to spur rural financing by the private sector that would help usher growth in the agriculture and rural areas. However, the rural areas have continued to suffer from the lack of access to financial services of banks. Despite government efforts to increase the flow of credit towards the rural sector, formal financial institutions have largely ignored the sector. Lack of financial depth and very limited access to financial services continue to hound the rural sector. Mapping out efficient rural finance policies and implementing them remain as critical challenges for policymakers. Although it is impossible to consider in this brief review paper many other interesting papers and studies on rural finance, the literature survey and the rural finance experiences discussed in the paper can hopefully motivate a policy research agenda on rural finance in the immediate future. This paper, thus, discusses recent new research findings and information on rural finance and suggests thematic areas for policy research.
Keywords: 330; asymmetric information; innovation; collateral substitutes; credit bureaus; risks and risk-mitigating instruments; transaction costs; Ländliches Finanzsystem; Kreditpolitik; Agrarkredit; Entwicklungsfinanzierung; Philippinen; Mikrofinanzierung